Strategy for Optimizing Orange Fruit Quality Using Technology: Case Study of Sidikalang Orange Farm - Harahap, Lokot Muda; Sidebang, Nitasari Lasma Uhur; Harahap, Gita Kusuma Dewi; Sitompul, Reginawati (Economic: Journal Economic and Business, 2024)
Oranges are one of the most consumed fruits worldwide, and Indonesia is one of the largest orange producers globally. However, the quality of oranges in Indonesia varies widely and is heavily influenced by seasonal and weather conditions. This study aims to optimize the quality of oranges using various modern technologies in an orange orchard in Sidikalang, Dairi Regency, North Sumatra. The research method used is a case study with a qualitative approach through observation and interviews. The results indicate that the use of technologies such as precision irrigation systems, soil sensors, and drones can enhance the size, color, texture, sugar content, and nutritional value of oranges. Additionally, these technologies improve production efficiency by reducing water and fertilizer use and lowering labor costs. However, the adoption of these technologies faces challenges such as high initial costs and the need for farmer training. Therefore, support from the government and financial institutions is essential to overcome these challenges and improve the quality of oranges in Indonesia.